Tourisme et paysages culturels : comparaison de la Valeur universelle exceptionnelle et de la mise en récit institutionnelle (UNESCO) de trois sites latino-américains - Elodie Salin (IdeAs)
Cultural landscapes, conceived by UNESCO as the combined works of man and nature, became an operating category of World Heritage in 1992. This article analyzes, through a comparative study, the processes of heritage, narrative and tourism in three landscapes in Latin-American cultures : Quebrada de Humahuaca (Argentina), agave landscape and ancient industrial facilities of Tequila (Mexico) and the cultural landscapes of Colombia’s coffee.